Adsorptive removal of congo red dye (CR) from aqueous solution by Cornulaca monacantha stem and biomass-based activated carbon: isotherm, kinetics and thermodynamics. Issue 6 (13th April 2019) - Sharma, Arush; Siddiqui, Zia Mahmood; Dhar, Sunil; Mehta, Pankaj; Pathania, Deepak
ABSTRACT: Cornulaca monacantha stem (CS) and biomass stem-based activated carbon (CS AC ) were explored for the removal of congo red (CR) dye from water system. The biomaterial was characterized using Fourier transform infrared spectroscopy (FTIR), Brunauer-Emmett-Teller (BET) and field emission scanning electron microscope (FESEM). The BET surface area of biomass stem-based activated carbon (CS AC ) was recorded to be 304.27 m 2 /g. The influence of different parameters such as initial CR concentration, adsorbent dosage, contact time, adsorbate pH and temperature onto CR adsorption were studied.The maximum adsorption of CR dye 97.19% and 86.43% were achieved at 55°C using CS AC and CS adsorbents, respectively. The isotherm, kinetics and thermodynamic study were also investigated to explore the adsorption mechanism. The adsorption isotherm closely follow the Langmuir model (R 2  = 0.99) suggesting the monolayer adsorption of CR dye. Kinetic results indicated that pseudo second-order and Elovich model provide the better regression coefficient. Thermodynamic study revealed the feasible, spontaneous and endothermic nature of adsorption process. The regeneration study implies that adsorbent was efficiently recovered from CR dye with 0.01 mol/L NaOH solution. The CS AC adsorbent possesses 75.75% uptake for CR dyes after 6th cycles of desorption-adsorption, respectively. .